Development of three‐dimensional laryngostroboscopy for office‐based laryngeal diagnostics and phonosurgical therapy. (17th October 2018) - Caffier, Philipp P.; Nawka, Tadeus; Ibrahim‐Nasr, Ahmed; Thomas, Björn; Müller, Holger; Ko, Seo‐Rin; Song, Wen; Gross, Manfred; Weikert, Sebastian
Abstract : Objective: To develop a three‐dimensional (3D) laryngostroboscopic examination unit, compare the optic playback quality in relation to established 2D procedures, and report the first case series using 3D rigid laryngostroboscopy for diagnosis and management of laryngotracheal diseases. Study Design: Laboratory study, prospective case series. Methods: The optical efficacy of newly developed rigid 3D endoscopes was examined in a laboratory setting. Diagnostic suitability was investigated in 100 subjects (50 male, 50 female) receiving 2D high‐definition (HD) and 3D laryngostroboscopy. Two of the subjects subsequently underwent 3D‐assisted office‐based transoral phonosurgery under local anesthesia. Main outcome measures were comparative visualization of laryngotracheal pathologies, influence on preoperative planning, and evaluation of prognostic factors for the outcome of phonosurgical interventions. Results: Three‐dimensional endostroboscopic procedures were effectively optimized to establish an examination protocol for all‐day clinical use. Office‐based 3D laryngostroboscopy was successfully applied in subjects with normal anatomy (n = 10) and various laryngotracheal findings (n = 90). In comparison to 2D HD videolaryngostroboscopy, the 3D view offered enhanced visualization of laryngotracheal anatomy, with qualitatively improved depth perception and spatial representation. In organic pathologies, this resulted in a more precise indication of phonosurgical procedures, increased accuracy in surgical planning, facilitated office‐based endoscopic surgery, and better evaluation of prognostic factors for the outcome of phonosurgical interventions. Conclusion: Three‐dimensional laryngostroboscopy proved to increase the understanding of functional and surgical anatomy. Its application has enormous potential for improving the diagnostic value of laryngoscopy, surgical precision in laryngotracheal interventions, tissue preservation, and methods of teaching. Level of Evidence: NA Laryngoscope, 128:2823–2831, 2018